Kurt Schwitters Archiv / Sprengel Museum Hannover - Sprengel Museum Hannover (2009)
[Dt.:] Kurt Schwitters Archiv und Werkverzeichnis mit Auskunft zu Werken, Fotobestellung, Publikationen und Informationen zu Symposien über Schwitters. - [Engl.:] Kurt Schwitters archive and list of works with information on his works, on ordering photographs, on publications and on symposia about Schwitters.